Implementation of a Strategic Maintenance Plan for a Telecommunications System and Its Relationship with the Operability of a Regional Hospital - Trujillo Guarderas, Giovanni León (2022)
This study aimed to determine the relationship between the implementation of a strategic maintenance plan and the operability of the telecommunications system at Hospital Docente Clínico Quirúrgico Daniel Alcides Carrión in Huancayo. A total of 33 hospital managers were included in the study population. The research approach is mixed and was applied to specific problems, circumstances and characteristics. A non-experimental, intentional, cross-sectional and descriptive-correlational design was used. A correlation coefficient of .656 with a p value = .000 < .01 was obtained for variables “implementation of the Strategic Maintenance Plan” and “operability of a telecommunications system of Hospital Docente Clínico Quirúrgico Daniel Alcides Carrión”. The results demonstrate that the implementation of a strategic maintenance plan guarantees the correct operation of a hospital’s resources.